Elastic Strain Energy Release at Failure and its Consequence for Structural Glass Testing and Design - Freek Bos (Challenging Glass Conference, 2016)
The amount of elastic strain energy that is being released upon initial failure of a structural glass element has profound influence on its post-initial failure load bearing capacity. This paper discusses the relevance of this notion to the evaluation of structural glass testing and the consequences it may have for structural glass design. It means, among others, that post-failure behaviour may be highly geometry dependent as well as strongly related to the cause of the initial failure (as both determine the amount of energy released at failure). The options to limit the consequences of energy release will be discussed. The result of application of one of these options to the design of reinforced glass beams is shown.